Increasing Therapist Productivity: Using Lean Principles in the Rehabilitation Department of an Academic Medical Center. Issue 5 (September 2017) - Johnson, Diana; Snedeker, Kristie; Swoboda, Michael; Zalieckas, Cheryl; Dorsey, Rachel; Nohe, Cassandra; Smith, Paige; Roche, Renuka
Abstract : Abstract: The Department of Rehabilitation Services, within the University of Maryland Medical Center's 650-bed academic medical center, was experiencing difficulty in meeting productivity standards. Therapists in the outpatient division believed they were not spending enough time performing billable patient care activities. Therapists in the inpatient division had difficulty keeping pace with the volume of incoming referrals. Collectively, these issues caused dissatisfaction among referral sources and frustration among the staff within the rehabilitation department. The department undertook a phased approach to address these issues that included examining the evidence, using Lean process improvement principles, and employing transformational leadership strategies to drive improvements in productivity and efficiency. The lessons learned support the importance of having meaningful metrics appropriate for the patient population served, the use of Lean as an effective tool for improving productivity in rehabilitation departments, the impact of engaging staff at the grassroots level, and the importance of having commitment from leaders. The study findings have implications for not only rehabilitation and hospital leadership, but CEOs and managers of any business who need to eliminate waste or increase staff productivity.